PELUANG HUBUNGAN KARAKTERISTIK MAHASISWA BARU DENGAN MOTIVASINYA MASUK ILMU KOMPUTER - syarif hidayatullah (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2020)
There are various motivational factors that can influence prospective new students at Pakuan University (UNPAK) when choosing a Computer Science (Ilkom) Department as their majors, including but not limited to: will be cooler or more powerful, make it easier to find jobs, increase knowledge, and make parents happy. Based on the survey, in this study we used the Chi Square method and the Bayes method to get the probability of the relationship between the characteristics of new students and their motivation to go to college when choosing a study program at the Faculty of Mathematics and Science at the UNPAK. The results show that there is a significant relationship between the characteristics of new students with motivation, which can be seen from the Gender, Regional Origin, Previous Information about Ilkom and Ilkom Media including those that are combined in the category except Gender. While the greatest opportunity occurred in the characteristics of new students to the motivation of 1; 0.806; 0.750 and 0.742.